Epigenetic pharmacology in aging: from mechanisms to therapies for age-related disorders - Yu, Haikuan; Feng, Taojin; Zhang, Chengcheng; Jiao, Zhouguang; Fan, Wenkai; Jiang, Rongxian; Kong, Dewen; Li, Fubing (Frontiers in Pharmacology, 2025)
Aging is a multidimensional process regulated by the interplay of genetic and environmental factors, with epigenetic alterations serving as a central regulatory hub. Aberrant DNA methylation patterns, dysregulation of histone-modifying enzymes (e.g., SIRT1, EZH2), and non-coding RNA-mediated mechanisms collectively remodel gene expression networks, impacting critical pathways such as cellular senescence and mitochondrial homeostasis. This establishes an “environment-epigenome-disease” causal axis, closely associated with pathologies including β-amyloid deposition in Alzheimer’s disease, atherosclerosis, immunosenescence, osteoporosis, sarcopenia, and tumorigenesis. Capitalizing on the reversible nature of epigenetic modifications, pharmacological epigenetics has emerged as a cutting-edge field for intervening in aging and age-related diseases. Targeting key epigenetic modifiers such as DNA methyltransferases and histone deacetylases enables the modulation of disease-associated epigenetic states, providing a promising avenue for therapeutic intervention in aging and age-related diseases. This review synthesizes the molecular mechanisms of epigenetic regulation in aging, their role in age-related diseases, and advances in pharmacological epigenetics—from basic research to clinical translation. It further situates key challenges such as target specificity, long-term safety, and tissue-specific delivery within a translational framework, aiming to inform strategies for the diagnosis and intervention of age-related conditions.